2015
DOI: 10.1128/cvi.00434-15
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with a Porcine Reproductive and Respiratory Syndrome (PRRS) Modified Live Virus Vaccine Followed by Challenge with PRRS Virus and Porcine Circovirus Type 2 (PCV2) Protects against PRRS but Enhances PCV2 Replication and Pathogenesis Compared to Results for Nonvaccinated Cochallenged Controls

Abstract: cCoinfections involving porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2) contribute to a group of disease syndromes known as porcine circovirus-associated disease (PCVAD). Presumably, PRRSV infection enhances PCV2 replication as a result of modulation of host immunity. The purpose of this study was to evaluate PCV2 replication and pathogenesis in pigs vaccinated with a PRRS modified live virus (MLV) vaccine and subsequently challenged with a combination of PRRSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…To evaluate host response to PRRS vaccination, half of the pigs in each trial were vaccinated with a modified live PRRSV 28 days prior to co-infection. Details of the design of these experiments, along with results for pathogenesis and the effects of PRRSV vaccination are in Niederwerder et al (2015). Results showed that vaccination to PRRS increased the impact of subsequent exposure to PCV2b, consistent with earlier findings that PRRSV infection weakens the immune system and increases the susceptible of pigs to other pathogens (Yin et al, 2013).…”
Section: Co-infection Trialssupporting
confidence: 81%
“…To evaluate host response to PRRS vaccination, half of the pigs in each trial were vaccinated with a modified live PRRSV 28 days prior to co-infection. Details of the design of these experiments, along with results for pathogenesis and the effects of PRRSV vaccination are in Niederwerder et al (2015). Results showed that vaccination to PRRS increased the impact of subsequent exposure to PCV2b, consistent with earlier findings that PRRSV infection weakens the immune system and increases the susceptible of pigs to other pathogens (Yin et al, 2013).…”
Section: Co-infection Trialssupporting
confidence: 81%
“…ORF1 encodes two replication-associated proteins (Rep and Rep=) which are necessary for the rolling-circle replication of viral DNA (5,8). ORF2 encodes the capsid protein (Cap), a unique structural component of the virion and the dominant immunogenic agent (3,4,9). Cap not only is indispensable for encapsulating the viral genome to assemble infectious virions but also is required for transport of the Rep protein and viral DNA between the cytoplasm and nucleus (10)(11)(12).…”
mentioning
confidence: 99%
“…For lungs, scores for microscopic lesions were assigned as described previously (Niederwerder et al., ) with minor modifications. Briefly, the scoring system is as follows: 0, no significant microscopic lesions; 1, mild interstitial pneumonia with <50% involvement in a single lobe; 2, mild to moderate multifocal interstitial pneumonia with 50%–75% involvement in one or two lobes; 3, severe multifocal interstitial pneumonia with 50%–75% involvement in one or two lobes; 4, severe diffuse interstitial pneumonia with >75% involvement in multiple lobes.…”
Section: Methodsmentioning
confidence: 99%